"A Road With No End": Making the South Pacific a Permanent Labour Reserve. Issue 5 (20th October 2022) - MacWilliam, Scott
ABSTRACT: Commencing in the 1980s and picking up pace over the last two decades, there has been a systematic campaign to construct a specific form of labour market in the South Pacific. Unskilled and semi-skilled workers are recruited on short-term contracts to work in agricultural industries in Australia and New Zealand. While the employment is on a casual basis, with workers required to return to home countries upon the completion of contracts, there is nothing temporary about the intent behind what are termed labour mobility programmes. This article examines the conditions in countries from which workers are recruited, where non-development reigns. Continuing internationalisation of agriculture, logging, mining, oil and gas production has undercut whatever existed as late colonial policy to bring national development. Low rankings on international indicators of health and literacy, widespread unemployment and under-employment, characterise populations where majorities are reproduced for the forms of labour required by labour mobility programme recruiters, local and international. Continuous shortages of labour for fruit picking and packing in the region's two largest economies are joined with relative surplus populations in nearby South Pacific countries. Temporary work is married to permanent accumulation on a road with no obvious end.